PENGARUH MODEL LEARNING CYCLE TERHADAP HASIL BELAJAR SENI RUPA KELAS VII DI SMP NEGERI 35 PADANG - Yuni Marpiah, Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2019)
This research aims to see the difference between visual art learning outcomes between the learning cycle model and the conventional model in class VII SMP Negeri 35 Padang. The research conducted is quantitative, quasi-experimental form (quasi-experiment), with a population of 159 students divided into 5 classes. The sampling technique used was random sampling to obtain classes VII.2 and VII.5. The results showed t count 2,548 and t table 1,999. From the above values, the calculated t value> t table value (2,548> 1,999). It can be concluded that the learning cycle model has an effect on student learning outcomes in the field of art in class VII SMP Negeri 35 Padang.Keywords: Cultural Arts, Fine Arts, Learning Cycle Model, Learning Outcomes